Ismideg awessar - Selim MOUSSAOUI (Altralang Journal)
ABSTRACT: Berber Onomastics is a field which is considered as a “Language Maintainer”. It strongly contributes to the construction of the newly developed language. By bringing meaningful nouns, that can take part in the archaïque lexis of the language. Despite the survival of the ancient form, these nouns can reappear having the same meaning as the old one or bring totally different meaning and context. Consequently, there is a strong relationship between the proper noun and the archaism, since most proper nouns, particularly typonyms, are archaic nouns, named long time ago. Then in the nick of time they lost their original meaning due to several resons, amongst them, the migration of the original populations from these places engendering the forgetfulness because of the non-use.